Creative Process Engagement Dan Intrinsic Motivation Sebagai Mediasi Humble Leadership Terhadap Employee Creativity - Nancy Rosminingsih Tomanda; Praptini Yulianti (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2021)
Creativity has an important role for organizations to implement new services and processes. This implies that employees in the organization must be creative to maintain organizational growth and to face today's business challenges.This Study aims to determine the relationship between humble leadership, creative process engagement, intrinsic motivation, and employee creativity. The study is quantitative with data collection methods using a questionnaire on 145 employees of PT Unilever Indonesia Tbk in the Customer development department and processed using analysis tools Partial Least Square (SmartPLS 3.0). The results show that humble leadership has a positive and significant effect on employee creativity when a leader applies the humble leadership style it will be able to increase the creativity of the employees. Creative process engagement mediates the relationship between humble leadership and employee creativity partially and intrinsic motivation partially mediates the relationship between humble leadership and employee creativity